IMPACT ON GOOD CORPORATE GOVERNANCE, FIRM SIZE AND LEVERAGE ON FINANCIAL PERFORMANCE INFRASTRUCTURE SECTOR - Huang, Felicia; Wijaya, Evelyn; Chandra, Jennifer; Martha, Martha; Triyonowati, Triyonowati (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Infrastructure development has a positive impact on social aspects and human development as well as strategic investment in economic growth and community welfare. This research aims to analyze the impact on Good Corporate Governance, Firm Size, and Leverage on Financial Performance Infrastructure Sector. This research uses secondary data, which is obtained from the companies' financial statements. The data collection technique used is purposive sampling. The sample size consists of 49 companies. The research method used is quantitative analysis with Smart PLS software. The results indicate that board of directors has a positive and significant impact on financial performance, while audit committee has a negative and significant impact on financial performance. board of commissioners, firm size, and leverage have no significant impact on financial performance. Pembangunan infrastruktur memberikan dampak positif pada aspek sosial dan pembangunan manusia serta investasi strategis dalam pertumbuhan ekonomi dan kesejahteraan masyarakat. Penelitian ini bertujuan untuk menganalisa pengaruh Good Corporate Governance, Firm Size dan Leverage terhadap Financial Performance sektor infrastruktur. Penelitian ini menggunakan data sekunder di mana data diperoleh berasal dari laporan keuangan perusahaan. Teknik pengumpulan data adalah teknik purposive sampling. Jumlah sampel dalam penelitian adalah 49 perusahaan. Metode analisa data menggunakan teknik analisis kuantitatif dengan software Smart PLS. Hasil penelitian menunjukkan bahwa dewan direksi berpengaruh positif dan signifikan terhadap financial performance dan komite audit berpengaruh negatif dan signifikan terhadap financial performance. Sedangkan untuk variabel dewan komisaris, firm size dan leverage berpengaruh tidak signifikan terhadap financial performance.